2015
DOI: 10.3748/wjg.v21.i19.6032
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection for early gastric cancer with undifferentiated-type histology: A meta-analysis

Abstract: In this analysis, ESD is a technically feasible treatment modality for EGC with undifferentiated-type histology. Long-term studies are needed to confirm these therapeutic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 49 publications
(92 reference statements)
2
30
0
Order By: Relevance
“…The complete resection rate with endoscopic resection was 85.0%, which was similar to the complete resection rate for differentiated EGCs in previous studies [1114]. Furthermore, this result was higher than that for undifferentiated EGCs that ranged from 60% to >80% in recent studies [212223]. Advances in endoscopic techniques and devices have increased the immediate clinical outcomes of patients with early GCLS.…”
Section: Discussionsupporting
confidence: 80%
“…The complete resection rate with endoscopic resection was 85.0%, which was similar to the complete resection rate for differentiated EGCs in previous studies [1114]. Furthermore, this result was higher than that for undifferentiated EGCs that ranged from 60% to >80% in recent studies [212223]. Advances in endoscopic techniques and devices have increased the immediate clinical outcomes of patients with early GCLS.…”
Section: Discussionsupporting
confidence: 80%
“…The therapeutic outcomes of ER of EGC with undifferentiated-type histology have previously been presented using a meta-analysis of small studies [ 7 ]. Although these data suggested the technical feasibility of ER of these lesions, the follow-up durations of the included studies were relatively short, and most studies did not present therapeutic outcomes divided by PDC and SRC.…”
Section: Introductionmentioning
confidence: 99%
“…Authors previously reported therapeutic outcomes of ESD for EGC-UH using pooled meta-analysis of crude outcomes of each study. [13] The common effect size will be extracted from each study using method previously described (pooled meta-analysis of crude outcomes) [13] , and we will also perform sensitivity and meta-regression analyses using the modifiers identified during the systematic review to confirm the robustness of the main result and to identify the reason of heterogeneity. If paucity data exist for endoscopic resection of EGC with PAC, the rate of LNM will be described and retrospective application of ESD criteria for surgically resected specimen will be performed, whenever possible.…”
Section: Methodsmentioning
confidence: 99%